Application of NFC Technology in Railway Passenger Transport by Introducing New Products - Brumercikova, Eva; Bukova, Bibiana; Kondek, Pavol; Drozdziel, Pawel (Communications - Scientific letters of the University of Zilina, 2017)
Near Field Communication (NFC) is a new trend in the world of information technology, which has a profound impact on all spheres of life. This technology is currently being applied in public transport services, which is confirmed by a number of passenger handling methods that use NFC throughout Europe. NFC technology offers convenience and mobility to users of public passenger transport. With NFC carriers may expand their portfolio of NFC supported services. This paper presents possible application of the NFC technology in railway passenger transport by introducing new products, and the possibility to expand the business portfolio of railway operators.